EVALUATING THE QUALITY OF UNINTENDED PREGNANCY SERVICES AT PKBI CLINIC DKI JAKARTA - Yunanda, Rista; Rahmaniati, Martya; Prasetyo, Sabarinah (Journal of Applied Health Management and Technology, 2024)
Based on WHO estimates, the unintended pregnancy rate in Indonesia is 40/1,000 women aged 15-49 years. PKBI clinic recorded 210 cases of unintended pregnancy from 2022 to 2024. These cases pose significant risks to maternal and child health. The high incidence of these cases necessitates the provision of high-quality services by health facilities. This is crucial to enhance patient satisfaction and improve service access. The objective of this study is to give an overview of the quality services evaluation for unintended pregnancy at PKBI Clinic. This study is a descriptive study using secondary data from the PKBI clinic based on monthly patient visits from 2022 to 2024.  The analysis uses a Run Chart and Control Chart. The results of the Run Chart analysis indicate the presence of common causes that remain under system control, whereas further analysis using Control Charts reveals the presence of special causes. These special causes are associated with patient surges at certain times and the impact of health education programs. However, to anticipate patient surges, the PKBI clinic is still lacking in human resources. This study concludes that Control Charts are more sensitive in detecting special causes due to the presence of control limits that can identify out-of-control data and detect small changes. The evaluation of service quality for unintended pregnancies at the PKBI clinic demonstrates good quality, but a lack of human resources can reduce this quality. Therefore, there is a need for additional staff, training, and better management of work schedules.